2022
DOI: 10.1002/hed.26993
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning directed sentinel lymph node biopsy in cutaneous head and neck melanoma

Abstract: Background The specificity of sentinel lymph node biopsy (SLNB) for detecting lymph node metastasis in head and neck melanoma (HNM) is low under current National Comprehensive Cancer Network (NCCN) treatment guidelines. Methods Multiple machine learning (ML) algorithms were developed to identify HNM patients at very low risk of occult nodal metastasis using National Cancer Database (NCDB) data from 8466 clinically node negative HNM patients who underwent SLNB. SLNB performance under NCCN guidelines and ML algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Liu et al investigated a deep learning-based AI algorithm called LYmph Node Assistant for the analysis of tissues and the recognition of metastases on whole-slide images. The authors observed an AUC of 99.3% and a sensitivity of 91.9% [26] . Oliver et al developed and tested multiple machine learning algorithms for the identification of patients with head and neck melanoma with a very low risk of occult lymph node metastasis, with the goal of avoiding the unnecessary and expensive use of SLN biopsy based on NCCN treatment guidelines.…”
Section: The Relevance Of Ai In the Management Of Esophageal Cancermentioning
confidence: 92%
“…Liu et al investigated a deep learning-based AI algorithm called LYmph Node Assistant for the analysis of tissues and the recognition of metastases on whole-slide images. The authors observed an AUC of 99.3% and a sensitivity of 91.9% [26] . Oliver et al developed and tested multiple machine learning algorithms for the identification of patients with head and neck melanoma with a very low risk of occult lymph node metastasis, with the goal of avoiding the unnecessary and expensive use of SLN biopsy based on NCCN treatment guidelines.…”
Section: The Relevance Of Ai In the Management Of Esophageal Cancermentioning
confidence: 92%
“…Real-time quantitative PCR on SNs is an area of exploration and shows potential for more accurate intraoperative identification of occult metastases [91,92] . The application of machine learning is also being explored to help identify pathological features that predict the risk of metastasis prior to surgical treatment [93,94] . The hope is to identify patients who are at higher risk and may benefit from SLNB or END versus observation.…”
Section: Future Directionsmentioning
confidence: 99%
“…In otolaryngology, for instance, AI and machine learning have been used for screening, diagnosis, and treatment decision in rhinology, 5 otology, 6 laryngology, 7 and head and neck oncology 8 . We have also previously demonstrated the utility of AI for predicting head and neck melanoma patients with a low risk of nodal metastasis 9 and identifying patients with oral cavity squamous cell carcinoma at risk for occult nodal disease 10 …”
Section: Introductionmentioning
confidence: 99%